Phase Composition and Microstructure of Ti-Nb Alloy Produced by Selective Laser Melting; IOP Conference Series: Materials Science and Engineering; Vol. 140 : Interdisciplinary Problems in Additive Technologies - Sharkeev Yu. P. Yury Petrovich; Eroshenko A. Yu.; Kovalevskaya Zh. G. Zhanna Gennadievna; Saprykin A. A. Aleksandr Aleksandrovich; Ibragimov E. A. Egor Arturovich; Glukhov I. A.; Chimich M. A.; Uvarkin P. V.; Babakova E. V. Elena Vladimirovna (2016, 2016)
Title screen